Facilitators and barriers for emergency department clinicians using a rapid chest pain assessment protocol: qualitative interview research - Julia Crilly; Jaimi H. Greenslade; Sara Berndt; Tracey Hawkins; Louise Cullen (BMC, 2020)
Abstract Background Guideline-based processes for the assessment of chest pain are lengthy and resource intensive. The IMProved Assessment of Chest Pain Trial (IMPACT) protocol was introduced in one Australian hospital Emergency Department (ED) to more efficiently risk stratify patients. The theoretical domains framework is a useful approach to assist in identifying barriers and facilitators to the implementation of new guidelines in clinical practice. The aim of this study was to understand clinicians' perceptions of facilitators and barriers to the use of the IMPACT protocol. Methods Guided by the theoretical domains framework, semi-structured interviews with nine ED clinical staff (medical and nursing) were undertaken in 2016. Content analysis was conducted independently by two researchers to identify those theoretical domains that facilitated or hindered protocol use. Results Domains most often reported as fundamental to the use of the IMPACT protocol included 'social/professional role and identity', 'environmental context and resources' and 'social influences'. These factors seemingly influenced professional confidence, with participants noting 'goals' that included standardisation of practice, enhanced patient safety, and reduced need for unnecessary testing. The domain 'environmental context and resources' also contained the most noted barrier - the need to inform new members of staff regarding protocol use. Opportunities to overcome this barrier included modelling of protocol use by staff at all levels and education - both formal and informal. Conclusions A range of domains were identified by ED staff as influencing their chest pain management behaviour. Fundamental to its use were champions/leaders that were trusted and accessible, as well as social influences (other staff within ED and other specialty areas) that enabled and supported protocol use. Research investigating the implementation and perceived use of the protocol at other sites, of varied geographical locations, is warranted.